Construct validity of the Danish version of the Work Rehabilitation Questionnaire (WORQ)—sensitivity and specificity of the objectively tested physical capacity items - Verpe, Ida Skovborg; Thygesen, Katrine Baltzer; Escorpizo, Reuben; Mortensen, Ole Steen; Korshøj, Mette (Frontiers in Rehabilitation Sciences, 2023)
Objective The aim of this study was to examine construct validity of the Danish version of the Work Rehabilitation Questionnaire (WORQ), and to compare the physical capacity items of WORQ to objective, standardized measures of physical capacity and to selected SF-36 physical items. Methods The study took place at the job center in Holbæk municipality and 40 clients of working age were enrolled. Participants completed the interviewer-administered version of WORQ, selected SF-36 items and underwent objective, physical capacity testing, including a 30-second sit-to-stand-test, a hand-grip-strength test and a six-minute-walk test to estimate cardiorespiratory fitness. Correlations between variables were assessed using Spearman’s correlation. Further, cross tabulations and chi-square testing were conducted and sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated. Results We found a moderate to strong correlation between WORQ- and SF-36 items and a weak to moderate correlation between physical capacity items of WORQ and objectively tested physical capacity measures. On the basis of cross tabulations, calculations yielded overall higher NPVs than PPVs, whereas sensitivity and specificity varied more with not one parameter being overall better than the other. Conclusion We found evidence of construct validity of the WORQ-Danish. But our study might also raise question as to whether objective physical capacity tests are the gold standard for evaluating functioning. Our results are promising and we suggest further investigations of the screening capabilities of WORQ, alongside with other legacy measures or instruments – both self-reported- and objective physical measures, to complement information - where specific answers to specific questions trigger work related actions or interventions